Site-specific Cleavage of BMP4 by Furin, PC6, and PC7 - Nelsen, Sylvia M. (American Society for Biochemistry and Molecular Biology, 2009)
Bone morphogenetic proteins (BMPs) require proteolytic activation by members of the proprotein convertase (PC) family. Pro-BMP4 is initially cleaved at a site adjacent to the mature ligand domain (S1) and then at an upstream site (S2) within the prodomain. Cleavage at the S2 site, which appears to occur in a tissue-specific fashion, regulates the activity and signaling range of mature BMP4. To test the hypothesis that tissue-specific cleavage of pro-BMP4 is regulated by differential expression of a site-specific protease, we identified the PCs that cleave each site in vivo. In Xenopus oocytes, furin and PC6 function redundantly to cleave both the S1 and S2 sites of pro-BMP4, as evidenced by the results of antisense-mediated gene knockdown and the use of the furin- and PC6-selective inhibitor α(1)-PDX. By contrast, α(1)-PDX blocked cleavage of the S2 but not the S1 site of pro-BMP4 in embryos, suggesting the existence of a developmentally regulated S1 site-specific convertase. This protease is likely to be PC7 based on knowledge of its required substrate cleavage motif and resistance to α(1)-PDX. Consistent with this prediction, an α(1)-PDX variant engineered to target PC7, in addition to furin and PC6, completely inhibited cleavage of BMP4 in oocytes and embryos. Further studies showed that pc7 transcripts are expressed and polyadenylated, and that the PC7 precursor protein undergoes efficient autocatalytic activation in both oocytes and embryos. These results suggest that PC7, or a convertase with similar substrate specificity, functions to selectively cleave the S1 site of pro-BMP4 in a developmentally regulated fashion.